Sexually dimorphic behavior, neuronal activity, and gene expression in Chd8-mutant mice. (September 2018) - Jung, Hwajin; Park, Haram; Choi, Yeonsoo; Kang, Hyojin; Lee, Eunee; Kweon, Hanseul; Roh, Junyeop; Ellegood, Jacob; Choi, Woochul; Kang, Jaeseung; Rhim, Issac; Choi, Su-Yeon; et al.
Abstract Autism spectrum disorders (ASDs) are four times more common in males than in females, but the underlying mechanisms are poorly understood. We characterized sexually dimorphic changes in mice carrying a heterozygous mutation inChd8 (Chd8 +/N2373K ) that was first identified in humanCHD8 (Asn2373LysfsX2), a strong ASD-risk gene that encodes a chromatin remodeler. Notably, although male mutant mice displayed a range of abnormal behaviors during pup, juvenile, and adult stages, including enhanced mother-seeking ultrasonic vocalization, enhanced attachment to reunited mothers, and isolation-induced self-grooming, their female counterparts do not. This behavioral divergence was associated with sexually dimorphic changes in neuronal activity, synaptic transmission, and transcriptomic profiles. Specifically, female mice displayed suppressed baseline neuronal excitation, enhanced inhibitory synaptic transmission and neuronal firing, and increased expression of genes associated with extracellular vesicles and the extracellular matrix. Our results suggest that a humanCHD8 mutation leads to sexually dimorphic changes ranging from transcription to behavior in mice. Autism is 4 times more common in males. Jung et al. reveal male-preponderant abnormal behaviors in mice lacking CHD8, a chromatin remodeler, accompanying sexually dimorphic changes in neuronal firing, synaptic transmission, and gene expression.